Analisis pengaruh harga, PDB dan nilai tukar terhadap ekspor Batu Bara Indonesia - Wijaya, KGS Anton; Nurjanah, Rahma; Mustika, Candra (e-Journal Perdagangan Industri dan Moneter, 2018)
The objectives of this study are as follows: (1) To determine and analyze the development of prices, GDP, exchange rates, and exports of Indonesian Coal. (2) To find out and analyze the effect of prices, GDP, and exchange rates on Indonesia's coal exports. Based on the study results, (1) The average coal export in Indonesia from 2002-2016 was 11.91 percent per year. The development of Indonesian Coal prices from 2002-2016 was 17.77 percent per year. The average growth of the exchange rate from 2002-2016 was 2.18 percent per year. The average development of Indonesia's GDP from 2002-2016 was 5.47 percent. (2) The regression results show that the price of coal and the exchange rate has significantly affect Indonesia's coal exports. This can be seen from the t-count > t-table. Meanwhile, GDP does not have a significant effect on Indonesia's coal exports.Â  Keywords: Price, GDP, Exchange rate, Coal export